1999
DOI: 10.1128/jvi.73.10.8040-8052.1999
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6B Genome Sequence: Coding Content and Comparison with Human Herpesvirus 6A

Abstract: Human herpesvirus 6 variants A and B (HHV-6A and HHV-6B) are closely related viruses that can be readily distinguished by comparison of restriction endonuclease profiles and nucleotide sequences. The viruses are similar with respect to genomic and genetic organization, and their genomes cross-hybridize extensively, but they differ in biological and epidemiologic features. Differences include infectivity of T-cell lines, patterns of reactivity with monoclonal antibodies, and disease associations. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(174 citation statements)
references
References 60 publications
4
164
0
4
Order By: Relevance
“…HHV-6 is a member of the Betaherpesvirinae subfamily. Two major subgroups with distinct genetic, immunological and virologic characteristics have been named as HHV-6A and HHV-6B [24][25][26][27][28] . Ichimi et al reported that in cord blood lymphocytes, HHV-6 induced apoptosis by an unknown mechanism, which was independent of death receptors [29] .…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 is a member of the Betaherpesvirinae subfamily. Two major subgroups with distinct genetic, immunological and virologic characteristics have been named as HHV-6A and HHV-6B [24][25][26][27][28] . Ichimi et al reported that in cord blood lymphocytes, HHV-6 induced apoptosis by an unknown mechanism, which was independent of death receptors [29] .…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of HHV-6A and HHV-6B range in length from 160 to 170 kb and encode approximately 100 proteins . The overall nucleotide sequence identity between HHV-6A and HHV-6B is approximately 90% (Dominguez et al, 1999). Eighteen open reading frames are unique to either HHV-6A or HHV-6B.…”
Section: Introductionmentioning
confidence: 99%
“…The genomes of HHV-6A and HHV-6B range in length from 160-170 kbp and encode approximately 100 proteins [ 144]. The overall nucleotide sequence identity between HHV-6A and HHV-6B is approximately 90% [145]. Of the genes with less than 70% identity between the two variants, all but one (U47) were found in the immediate-early region [145].…”
Section: Hhv-6 and Msmentioning
confidence: 99%
“…The overall nucleotide sequence identity between HHV-6A and HHV-6B is approximately 90% [145]. Of the genes with less than 70% identity between the two variants, all but one (U47) were found in the immediate-early region [145]. Eighteen open reading frames are unique to either HHV-6A or HHV-6B.…”
Section: Hhv-6 and Msmentioning
confidence: 99%
See 1 more Smart Citation